Vacuum energy and cosmological supersymmetry breaking in brane worlds - Gravanis, Elias; Mavromatos, Nick E. (My University, 2002)
In the context of a toy model we discuss the phenomenon of colliding five-branes, with two of the extra space dimensions compactified on tori. In one of the branes (hidden world) the torus is magnetized. Assuming opposite-tension branes, we argue that the collision results eventually in a (time-dependent) cosmological vacuum energy, whose value today is tiny, lying comfortably within the standard bounds by setting the breaking of the four-dimensional supersymmetry at a TeV scale. The small value of the vacuum energy as compared with the supersymmetry-breaking scale is attributed to transient phenomena with relaxation times of order of the age of the Universe. An interesting feature of the approach is the absence of a cosmic horizon, thereby allowing for a proper definition of an S-matrix. As a result of the string non-criticality induced at the collision, our model does not provide an alternative to inflation, given that arguments can be given supporting the occurrence of an inflationary phase early after the collision. The physics before the collision is not relevant to our arguments on the cosmological constant hierarchy, which are valid for asymptotically long times after it. © 2002 Elsevier ]Science B.V. All rights reserved.
Keywords: Algebra; Modules; Logarithmic conformal